Unveiling the Obstacles: Tackling Challenges in Public Basic School Management - Moses Adeleke Adeoye; Rasheedat Modupe Oladimeji; Jubril Olaniyi Ayuba; Yusuff Olatunji Abimbowo (Undiksha Press, 2024)
This research identifies and examines these obstacles, providing insights into potential solutions to enhance school management in Nigeria. The primary research objectives include understanding the key issues affecting public basic schools and proposing actionable strategies for improvement. This research employs a qualitative approach, utilising a comprehensive literature review as the primary method for data collection. The research subjects encompass school administrators, teachers, and other stakeholders involved in basic public-school management. Data was collected through an extensive review of existing studies, policies, and academic papers related to the subject, which helped identify gaps in the current body of knowledge. For data analysis, thematic analysis was employed to interpret the findings, allowing for a detailed understanding of the challenges faced by public basic schools. The results indicate that significant barriers include inadequate infrastructure, such as a shortage of classrooms and sanitation facilities and a lack of essential educational resources like textbooks and stationery. These issues contribute to overcrowded classrooms and unsanitary conditions, adversely affecting students' health and learning outcomes. In conclusion, addressing basic public school management challenges requires a multifaceted approach that includes infrastructure development, resource allocation, and administrative reforms. By tackling these barriers, stakeholders can create an educational environment that fosters holistic development, empowers educators, and equips learners with the necessary skills to thrive in the 21st century.